Business model innovation: Strategic expansion of German small and medium wineries into hospitality and tourism - Marc Dressler; Ivan Paunović (Administrative Sciences, 2021)
This article provides insights into the modalities of business-model change and innovation. On the basis of an analysis of empirical data of small and medium enterprises, a transition from wine production centrism to its expanded use in hospitality and tourism is explored. Previous research on wine tourism and hospitality predominantly focuses on a destination perspective, neglecting the organizational winery perspective. The article deploys a mixed methods approach, combining netnography and a content analysis for data collection with grounded research and clustering for theory building. The sample size included 885 German wineries. Data stemmed from two distinct sources (websites and a secondary publication in form of a wine guide) and has been analyzed through a two-step clustering algorithm as well as a Principal Component Analysis (PCA). The two-step clustering algorithm resulted in nine different business models while the PCA analysis grouped the variables into the following two categories: basic winery business model (BM) and BM extension into hospitality and tourism, thereby validating the difference between the two constructs. The results point to the diverse nature of business model extensions of wineries in tourism and hospitality, depending on their organizational type and size. This study offers a classification of small and medium sized enterprise's strategic business model expansion, and explores the expansion of the wine industry through wine hospitality and tourism services, starting with the winery organizational perspective, which has not been done before.
Keywords: 350; entrepreneurship; small business; business model extensions; SME; wine hospitality; wine tourism